Anisotropic stretch biases the self-organization of actin fibers in multicellular Hydra aggregates - Anaïs Bailles; Giulia Serafini; Heino Andreas; Christoph Zechner; Carl D. Modes; Pavel Tomancak (Proceedings of the National Academy of Sciences, 2025)
During development, groups of cells generate shape by coordinating their mechanical properties through an interplay of self-organization and prepatterning. Hydra displays a striking planar pattern of actin fibers at the organism scale, and mechanics influence the morphogenesis of biological structures during its prepatterned regeneration. However, how mechanics participate in the formation of an ordered pattern from a totally disordered state remains unknown. To study this, we used cellular aggregates formed from dissociated Hydra cells, which initially lose all actin polarity yet regenerate a long-range actin pattern. We showed quantitatively that the actin meshwork evolves from a disordered symmetric state to an ordered state in which rotational symmetry is broken, and translation symmetry is partially broken, with the nematic and smectic order parameters increasing over days. During the first hours, the actin meshwork displayed spatial heterogeneity in the nematic order parameter, and ordered domains separated by line defects progressively grew and fused. This suggests that local cell–cell interactions drive the transition from disorder to order. To understand the mechanism of ordering, we perturbed the tissue’s physical constraints. We showed that while topology and geometry do not have a direct effect, anisotropic stretch biases the emerging orientation of the actin meshwork within hours. Surprisingly, although a Wnt head organizer is expected to play a role in the actin ordering, the stretch-associated alignment happened without the prior formation of a head organizer. This demonstrates the role of tissue mechanics in the alignment of the actin fibers during the disorder-to-order transition.